Effect of Au diffusion in Au-coated (γ + α2) titanium aluminides. (March 2018) - Bacos, Marie-Pierre; Perrut, Mikael; Boivin, Denis; Horezan, Nicolas; Rimpot, Etienne; Rio, Catherine; Sanchez, Claire
Abstract: In order to understand the role of α2 -Ti3 Al precipitates during the oxidation of Au-coated γ-48-2-2-TiAl alloys, the γ-TiAl and α2 -Ti3 Al microstructures resulting from Au diffusion at 900 °C were investigated. The as-obtained coatings were characterized using scanning electron microscopy (SEM), combined energy and wavelength dispersive X-ray spectroscopies (EDS, WDS), electron backscatter diffraction analysis (EBSD), X-ray diffraction (XRD) and isothermal oxidation tests. Results showed that Au-coated-γ-TiAl alloys presented an upper aluminoformer TiAlAu2 layer and a lower non-protective TiAlAu layer, both with narrow homogeneity range, and with thicknesses that could be estimated with the use of the Prasad model. A more complex layer structure is obtained after Au diffusion in α2 -Ti3 Al alloys, since eight different phases were identified. In the lower layers, two new ternary tetragonal phases (Ti2 AlAu and Ti3 Al2 Au) were found, and a partial diagram for the Al-Au-Ti 900 °C isotherm is proposed. Absence or depletion of Al was found in the upper layers and, in addition, a low oxidation resistance of the Au-coated-α2 -Ti3 Al alloy was reported. Highlights: The characterization of Au-diffused coatings on α2 Ti3 Al is presented. One partial 900 °C isothermal section of Al–Au–Ti is established. Two new ternary Ti2 AlAu and Ti3 AlAu compounds were identified.